Effect of pituitary extract, ovaprim and combination of human chorionic gonadotropin and metoclopramide on reproductive performance of Caspian shemaya, Alburnus chalcoides (Guldenstadt, 1772) - Nosrati, Majid; Khara, Hossein; Vahabzadeh, Habib; Mirhashemi Nasab, Sayeed Fakhredin (Indian Journal of Fisheries, 2019)
The present study was conducted to examine the effects of three different hormonal treatment types i.e., pituitary extract (Pt), ovaprim (Ov) and human chorionic gonadotropin (HCG) + Metoclopramide (Met) on reproductive performance of Caspian shemaya, Alburnus chalcoides (Guldenstadt, 1772). To this end, three experimental treatments and one control group were considered. The experimental groups were administrated with different doses of Pt, Ov, HCG + Met as follows: Pt [2 mg kg bw (body weight)-1], Pt (3 mg kg bw -1), Pt (4 mg kg bw -1), Ov (10 Î¼g kg bw -1), Ov (20 Î¼g kg bw -1), Ov (30 Î¼g kg bw -1), HCG + Met (1000 IU kg bw -1), HCG + Met (2000 IU kg bw -1), HCG + Met (3000 IU kg bw-1) and also a control group without any hormonal treatment. The highest values of oocyte weight and egg diameter were observed in groups administrated with Ov (10 Î¼g kg bw-1) and HCG + Met (2000 IU kg bw-1) respectively. The highest values of absolute fecundity and relative fecundity were recorded for fish administrated with Ov (20 Î¼g kg bw-1). The latency period and hour-degree for final maturation were lower in fish administrated with Ov (10 Î¼g kg bw-1) compared to other experimental groups (p